EFFECTIVENESS OF ELECTRONIC MEDICAL RECORD INFORMATION SYSTEMS IN SUPPORTING HEALTH SERVICES AT COMMUNITY HEALTH CENTERS - Hartati, Sri; Tosepu, Ramadhan (Universitas Halu Oleo, 2024)
ABSTRACT Recording medical records in paper form certainly has several risks, such as writing errors, duplicate notes, and taking a long time to write, as well as taking a long time to search for patient medical record data. This condition can disrupt the quality of health services at Community Health Centers. This research aims to determine the effectiveness of the electronic medical record information system in supporting health services at community health centers. The research method uses qualitative research methods to describe problem solving descriptively. Data analysis using a qualitative descriptive approach is used to find out how to solve problems, then draw conclusions. The research results show the effectiveness of the electronic medical record information system through a tracer application based on a desktop system that uses a database server. This system must be supported by quality human resources so that its operation is easier, more attractive and speeds up the work of health workers in processing patient data, staff data, family data, diagnosis data and treatment data. Other factors such as the influence of the budget need to be studied to support the effectiveness of electronic medical records in managing health services at community health centers. Keywords: Electronic Information Systems, Health Services, Medical Records.